SUBSTANTIATING THE EXPEDIENCY OF DIFFERENT TREATMENT METHODS OF CAT UROLITHIASIS - Firsova, Ye. S.; Kanivets, N. S.; Bezdyelna, A. S.; Khomenko, A. M. (Scientific Progress & Innovations, 2019)
This review article contains the analyzed and generalized information about the treatment of domestic cats suffering from urolithiasis. The explanations as to the types of urinary calculi, the expediency of using conservative or surgical treatment are presented in the article. Cat urolithiasis can be referred to as one of the most widely spread pathologies of pets. This disease is equally registered among males and females. The clinical picture of urolithiasis has characteristic features. However, in some cases, the relevant symptoms can be smoothed or even absent. Therefore, the treatment of cat urolithiasis must be complex and substanti-ated in each case, because without determining the origin and mineral composition of the stones, the treat-ment may not help, but even significantly worsen the condition of the diseased animal. Besides, the correct diagnosing makes it possible to apply therapeutic methods that are the least traumatic for the patient. Taking into account the presented data, the correct diagnostics is the basis of the appropriate treatment for urolithi-asis. The urine pH has a significant effect on lithogenesis, in particular: struvites, calcium carbonate, urates are less soluble in alkaline urine, cystine is less soluble in acidic urine. For silicate stones urine pH has no effect. For example, medicamental treatment is expedient for struvite and cystine stones (using Allopurinol, Thiol, Tiopronin, etc.). For uroliths of calcium oxalate and majority of urates, minimally invasive removal is used (intra-corporal laser lithotripsy, urohydropropulsion, cystolithotomy etc.). Urethrotomy and urethros-tomy should be conducted in urgent cases, as surgical interventions not only increase the risk of recurrence, but can also lead to permanent changes in the anatomy and functions of the urinary system. Therefore, with this pathology of the urinary system, constant diet therapy with the appropriate correction and regular ex-aminations by veterinary doctor are necessary. The information provided can be used in scientific research-es. In addition, the data summarized in the article will help specialists to choose the methods of treatment cat urolithiasis and provide new information that can be used in the prevention of this disease.